137k views
1 vote
Rewrite the following expression using the properties of rational exponents. Be sure your answer is in simplest form.

(2•6)3/2​

User Qzb
by
5.2k points

1 Answer

3 votes

Answer:


(2\cdot 6)^{(3)/(2)}=24(3)^{(1)/(2)}

Explanation:

The given expression is
(2*6)^{(3)/(2)}

We multiply within the parenthesis to get:


(12)^{(3)/(2)}

Recall that:
a^{(m)/(n) } =\sqrt[n]{x^m}

We apply this property to get:


(12)^{(3)/(2)}=√(12^3)


(12)^{(3)/(2)}=√(12^2*12)

This simplifies to


(12)^{(3)/(2)}=12√(12)

We can simplify further


(12)^{(3)/(2)}=12√(4*3)=12*2√(3)=24√(3)

We rewrite as rational exponent
24(3)^{(1)/(2)}

User Fjodr
by
5.0k points